Colluding clique detector based on activity similarity in P2P trust model - MIAO Guang-sheng; FENG Deng-guo; SU Pu-rui (Tongxin xuebao)
Colluding clique has become the first threat to trust model. However, today’s trust models in P2P network are known as green hand in handling colluding cliques. CCD, a colluding clique detector, was proposed to detect the exis-tence of colluding clique by measuring similarity of peer’s activities, which included a mathematical description and a distributed implementation. The simulation results show that CCD is considerably effective in detecting colluding cliques and trust model with CCD is more reliable and has higher success rate than the same trust model but without CCD espe-cially when many colluding cliques exist.